Resolvins suppress tumor growth and enhance cancer therapy - Sulciner, Megan L.; Serhan, Charles N.; Gilligan, Molly M.; Mudge, Dayna K.; Chang, Jaimie; Gartung, Allison; Lehner, Kristen A.; Bielenberg, Diane R.; Schmidt, Birgitta; Dalli, Jesmond; Greene, Emily R.; Gus-Brautbar, Yael; et al. (The Journal of experimental medicine, 2018)
Cancer therapy reduces tumor burden by killing tumor cells, yet it simultaneously creates tumor cell debris that may stimulate inflammation and tumor growth. Thus, conventional cancer therapy is inherently a double-edged sword. In this study, we show that tumor cells killed by chemotherapy or targeted therapy (“tumor cell debris”) stimulate primary tumor growth when coinjected with a subthreshold (nontumorigenic) inoculum of tumor cells by triggering macrophage proinflammatory cytokine release after phosphatidylserine exposure. Debris-stimulated tumors were inhibited by antiinflammatory and proresolving lipid autacoids, namely resolvin D1 (RvD1), RvD2, or RvE1. These mediators specifically inhibit debris-stimulated cancer progression by enhancing clearance of debris via macrophage phagocytosis in multiple tumor types. Resolvins counterregulate the release of cytokines/chemokines, including TNFα, IL-6, IL-8, CCL4, and CCL5, by human macrophages stimulated with cell debris. These results demonstrate that enhancing endogenous clearance of tumor cell debris is a new therapeutic target that may complement cytotoxic cancer therapies.